2019
DOI: 10.1039/c9an00443b
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor surface functionalization by a simple photochemical immobilization of antibodies: experimental characterization by mass spectrometry and surface enhanced Raman spectroscopy

Abstract: Thirty seconds of appropriate UV irradiation brings about specific thiol formation in IgGs that allows them to bind “side on” on a thiol reactive surface, thereby making such a photochemical approach a valuable tool for surface functionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 62 publications
0
53
0
Order By: Relevance
“…The adopted functionalization procedure was the photochemical immobilization technique (PIT) [ 31 ], a powerful and quick methodology based on an appropriate UV-activation of Abs, whose effectiveness was already confirmed in several application for biosensing [ 6 , 8 , 10 , 32 , 33 , 34 ]. It was demonstrated that this method leads at the same time to a strong (covalent) binding of Abs onto gold surfaces while orienting Abs with one fragment antigen-binding site (Fab) exposed to the solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adopted functionalization procedure was the photochemical immobilization technique (PIT) [ 31 ], a powerful and quick methodology based on an appropriate UV-activation of Abs, whose effectiveness was already confirmed in several application for biosensing [ 6 , 8 , 10 , 32 , 33 , 34 ]. It was demonstrated that this method leads at the same time to a strong (covalent) binding of Abs onto gold surfaces while orienting Abs with one fragment antigen-binding site (Fab) exposed to the solution.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the functionalization procedure, the photochemical immobilization technique (PIT) recently introduced by Della Ventura et al [ 31 ] not only was used for the first time to functionalize a ME material (coated with gold), but also the gold nanoflowers grown on the magnetic nanoparticles. This technique, based on a controlled UV-activation of Abs, has proven to be an effective [ 6 , 8 , 10 , 32 , 33 , 34 ] and competitive methodology since it is rapid and user-friendly and leads to strong (covalent) and conveniently oriented bonds of Abs on the sensor surfaces, without affecting the intrinsic selectivity of the antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Gold NPs on the surface were functionalized with pan malaria antibodies (anti-PLDH) using PIT 39,49,50 . Such a technique consists of UV irradiation of Abs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to their moderate long-time stability and the need to immobilize them both with the right orientation and high surface density, the accomplishment of a robust and effective Ab surface functionalization is still an open issue 38 . In this respect, the well-established photochemical immobilization technique (PIT) is a simple, fast and effective strategy to tether Abs onto gold surfaces with one fragment antigen-binding (Fab) exposed to the surrounding environment 39 . Besides antibodies, aptamers are nucleic acids which have been evolved to bind to targets through molecular evolution approaches as alternative class of bioreceptors.…”
mentioning
confidence: 99%
“…20 The Photochemical Immobilization Technique (PIT) is a surface functionalization procedure that only requires UV activation of the Abs and leads to a high density functionalized surface within minutes. 21,22 PIT has proven itself to be effective in tethering Abs upright not only on flat surfaces, [23][24][25][26] but also on AuNPs, which were used either to ballast small antigen 27 or to realize a colorimetric biosensor for detecting IgGs 28 and estradiol. 29 In the latter cases, the presence of the antigen was detected as a change in the absorbance that can be easily measured by a spectrophotometer or even by naked eye.…”
mentioning
confidence: 99%